Economic impacts of a rural-to-urban water transfer: a case study of Crowley County, Colorado - Taylor, R. Garth, author; Young, Robert A. (Robert Alton), 1931-, author; McKean, John R., 1939-, author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1993)
Urban water supply agencies seeking to meet growing municipal water demands in the arid southwest are finding that the purchase of water from existing agricultural uses is, from their perspective, often more cost-effective than construction of additional storage. Colorado municipalities have been among the most active purchasers of irrigation water rights. Agriculture-to-urban water transfers have economic impacts at the local, regional and state levels. Although the transfers represent "willing buyer-willing seller" exchanges, and represent a gain for both parties to the transactions, concerns have been voiced over whether the economic values of the transacting entities fully take into account the values to the region and the state. Starting in the 1970s, water for urban use has been purchased in Crowley County, a small rural county in southeastern Colorado. Crowley County lands are irrigated from the Lower Arkansas River via the Colorado Canal. Some 85% of the water rights formerly serving 47,000 irrigated acres in Crowley County have been purchased by municipalities. This study had two main purposes. The first was to employ a nonmarket valuation technique to estimate the foregone direct economic benefits (opportunity costs) of irrigation water used in Crowley County. The second purpose was to estimate regional (direct plus secondary) employment impacts of the reduced irrigated agriculture.
November, 1993.
Keywords: Water transfer -- Economic aspects -- Colorado -- Crowley County -- Computer simulation; Water rights -- Economic aspects -- Colorado -- Crowley County -- Computer simulation